2016
DOI: 10.1002/chem.201600513
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Flavanthrone Derivatives: Synthesis, Characterization, and Application to Organic Light‐Emitting Diodes

Abstract: Simple modification of benzo[h]benz[5,6]acridino[2,1,9,8-klmna]acridine-8,16-dione, an old and almost-forgotten vat dye, by reduction of its carbonyl groups and subsequent O-alkylation, yields solution-processable, electroactive, conjugated compounds of the periazaacene type, suitable for the use in organic electronics. Their electrochemically determined ionization potential and electron affinity of about 5.2 and -3.2 eV, respectively, are essentially independent of the length of the alkoxyl substituent and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 64 publications
1
17
0
Order By: Relevance
“…This may become a crucial factor, when OLED lighting goes into mass production. [4,61,62] Therefore, alternative materials, such as Cu(I) complexes [2][3][4][5][6]27,[29][30][31][32][33][34][35][36][37][38][39][40][41][43][44][45]61, or purely organic molecules [92][93][94][95][96][97][98][99][100][101][102][103][104][105][106][107] came into the focus of research. In the scope of this work, we will concentrate on Cu(I) compounds.…”
Section: Introductionmentioning
confidence: 99%
“…This may become a crucial factor, when OLED lighting goes into mass production. [4,61,62] Therefore, alternative materials, such as Cu(I) complexes [2][3][4][5][6]27,[29][30][31][32][33][34][35][36][37][38][39][40][41][43][44][45]61, or purely organic molecules [92][93][94][95][96][97][98][99][100][101][102][103][104][105][106][107] came into the focus of research. In the scope of this work, we will concentrate on Cu(I) compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Molecules based on 4 with further fused benzene rings have been reported as potential energy storage materials 4 and also for use in OLEDs. 5 Here we report the remarkable direct oxidation of 1,5bis(dimethylamino)naphthalene 8 to the dication 9, which contains the bis N-methylated derivative of 4 as a core and bearing two dimethylamino substituents to stabilise the charge.…”
Section: Introductionmentioning
confidence: 90%
“…These authors demonstrated that indanthrone (6,15-dihydrodinaphtho-[2,3a:2 ,3 -h]phenazine-5,9,14,18-tetraone) an old, nitrogen containing insoluble dye can be converted into a solution processable azaacene, namely tetraoctyloxydinaphtho[2,3-a: 2 ,3h]phenazine, in a simple one-pot process consisting of carbonyl groups reduction with sodium dithionite, followed by o-alkylation under phase transfer catalysis conditions (see Figure 3a). Continuing their research on nitrogen-containing vat dyes as substrates for the preparation of azaacenes Kotwica et al [61,62] prepared a series of solution processable fused azaacenes, namely 8,16-dialkoxybenzo[h]benz [5,6]acridino[2,1,9,8-klmna]acridines from flavanthrone (benzo[h]benz [5,6]acridino [2,1,9,8-klmna]acridine-8,16-dione)-an almost forgotten dye (see Figure 3b). Very similar phenazine derivatives were obtained by oxidation of dialkyl-substituted 2-aminoanthraquinone with 2,3-dichloro-5,6-dicyanobenzenequinone [63].…”
Section: Synthesis Of Azaacenesmentioning
confidence: 99%
“…Consistent with these finding it emits ultraviolet radiation. [63], 37 [60], 38 [90], 39 [61], 40 and 41 [91], 42 [64]. R1 and R3 = (triisopropylsilyl)ethynyl, R2 = octyl group.…”
Section: Nonlinear Azaacenesmentioning
confidence: 99%